Extracts and Fractions of Green Tea (Camellia Sinensis L. Kuntze) as Antibiofilm on Staphylococcus Aureus ATCC 25923 - Wardani , Tatiana Siska; Erikania, Susanti; Al-Fajri , Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
In this study, the potency of extract and fraction (water, n-hexane ethyl acetate) from green tea leaves to inhibit biofilm formation and to degrade of biofilm produced by S. aureus ATCC 25923 were evaluated. The total phenolic content of green tea leaves was determined using spectrophotometry UV visible on λ=646 nm. Green tea leaves were macerated with 96% ethanol then were fractionated with water, ethyl acetate and n-hexane solvents. DO value (optical density) optimization. inhibition and degradation of biofilms were carried out through the microtiter plate method (using 96 wells), followed by using a microplate reader on λ = 595 nm. Then, the total phenolic content of the extract and fraction by spectrophotometry were determined. The results showed that IC50 value from extracts, water fraction, ethyl acetate fraction and n-hexane to inhibit S. aureus ATCC 25923 biofilms were 2,32; 4,04; 2,55; and 2,30 mg/mL respectively. EC50 values of extract, water fraction, ethyl acetate fraction and n-hexane to degrade S. aureus ATCC 25923 biofilms were 3,33; 3,33; 4,14; and 3,28 mg/mL. Total phenolic contains from extracts, water, ethyl acetate, and n-hexane fractions were 8.97; 6.729; 7.26; and 7.82 %. These results indicate that green tea leave has the potential antibiofilm for S. aureus ATCC 25923.